Genetic characterization of wheat genes resistance to tan spot and leaf rust - Sun, Xiaochun (Kansas State University, 2009)
Tan spot, caused by Pyrenophora tritici-repentis (Ptr), is an economically important foliar disease worldwide. Race 1 of the fungus, which produces the necrosis toxin Ptr ToxA and the chlorosis toxin Ptr ToxC, is the most prevalent race in the Great Plains of the United States. The purposes of this study are to 1) identify and map novel quantitative trait loci (QTL) involved in resistance to tan spot race 1 in common wheat (Triticum aestivum L.) and 2) explore the inverse gene-for-gene interaction in the wheat-P. tritici-repentis pathosystem. A population of 288 F2:6 recombinant inbred lines (RILs) developed from the cross between Chinese landrace WSB (resistant) and Ning7840 (highly susceptible) was firstly used to identify genomic regions harboring novel sources of resistance. Two QTLs associated with resistance to chlorosis were mapped to the short arm of chromosome 1A and 2B in the WSB/Ning7840 population. No interaction was found between the two QTL. To further explore the specific wheat-ToxC model, three other populations were developed based on two susceptible parents, Ning7840 and Wheaton. QTL analysis revealed that common QTL were detected in populations shared with the same susceptible parents. The observations suggested that susceptibility rather than resistance for tan spot chlorosis is specific and presented evidence for the inverse gene-for-gene theory in the WSB-ToxC pathosystem. Leaf rust, caused by Puccinia triticina Eriks., is another important foliar disease of common wheat worldwide. The rust-resistance genes Lr41 and Lr42 from T. tauschii accessions TA2460 (Lr41) and TA2450 (Lr42) have been used as sources of rust resistance in breeding programs. Molecular markers linked to these genes are essential tools for gene pyramiding. Two BC3F2:6 mapping populations were evaluated for leaf rust resistance at both seedling and adult plant stages and analyzed with simple sequence repeat (SSR) markers. Both genetic and physical mapping confirmed that markers linked to Lr41 and Lr42 were on chromosome arm 2DS and 1DS, respectively. Marker analysis in a diverse set of wheat germplasm indicated that tightly linked markers for Lr41 and Lr42 can be used for marker-assisted selection (MAS) in breeding programs.
Keywords: Wheat; pathogen; leaf rust; tan spot; mapping; QTL; Agriculture, Agronomy (0285)